Technology, wealth and modern management of technology - Dolinšek, Slavko (Managing global transitions, 2012)
In the paper, we propose somewhat different conceptualizations of technology, of a fundamental relationship between technology and wealth in a society, of technological capability, and of management of technology. We based our proposed conceptualizations on the current general and relevant technological practice. In order to infer these conceptualizations, we studied today's largest companies worldwide in different production and technology sectors as well as some general reporting on technology from technology-oriented media. These fundamental conceptualizations may be of interest to all those who are practically or theoretically concerned with technology, wealth, technological capability and management of technology, and who want to comprehend the essence of technology and its relations to phenomena, such as wealth and management ('to get the big picture'). At the end, we explain why there is a need in modern companies to manage technologies and what a new paradigm of management of technology is, i. e. what new challenges and trends a modern management of technology has to face.
Keywords: bogastvo; management; technological capabilities; technology; tehnologija; tehnološke sposobnosti; trendi; trends; wealth